MENCIPTAKAN HIGHER EDUCATION SUSTAINABLE DEVELOPMENT MELALUI INTELLECTUAL CAPITAL UNTUK MEMPERKUAT DAYA SAING PERGURUAN TINGGI DI INDONESIA - Wa Ode Zusnita Muizu; Ernie Tisnawati Sule (PEKBIS, 2018)
The vision of Indonesia 2030, the Indonesian economy is targeted to enter the top 5world economic power, with economic growth above 7 percent, per capita income ofabout US $ 18 thousand and the population of 285 million people. To achieve that,the economy is focused on industrialization, service and trade as a catalyst forcapital accumulation. In addition, the quality of community life should be modern andequitable, marked the entry of Human Resources (HR) Indonesia in the top 30human development index (HDI) in the world. Since 1990, in Malaysia andSingapore, the pattern of education that leads to the results of research andcompetence of human resources output has been implicated for a long time.Information from the Ministry of Manpower also revealed that Indonesia's educationlevel is still low (53 percent of elementary school), low productivity (marked byunemployment of educated workers and lack of inventions or applied research inscience and technology), competitiveness is low. This affects the performance of theeconomy. As a result, IMD World Competiveness Yearbook 2005 outlines, from 60countries of the world, Indonesia's economic performance rankings are in the orderof 60 or the last. This is the weakness of the education model in Indonesia, whichcan not be equated with outside education. Especially higher education. What is theend result of our higher education? Not clear! Then arise the phenomenon of"contribute" our education with indicators such as: printing many educatedunemployed (coming from college); printing many scholars but not synergizing withthe needs of the business world and industry; and print human resources but lackthe competence and skill that clearly fit the field. The competitiveness of the nationno longer rests on the richness of natural resources, but is increasingly determinedby innovation (technology) and human creativity in utilizing science. This meanshuman resource education and training, the key to shaping human capital. too early.The intellectual capital approach has become the talk of many universities, due tothe fact that the university's primary goal is the production and dissemination ofknowledge and other important emphasis is on research and human resources.(Elena, 2004), so the input and output are mostly composed of intangibles.Therefore, this seems inconsistent where there is greater development ofscholarship assessment and management of intangibles for business than highereducation institutions such as universities.